Second Opinion Assessment in Diagnostic Mammography at a Breast Cancer Centre - Lorenzen, J.; Finck-Wedel, A. K.; Lisboa, B.; Adam, G. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: The aim of this retrospective study was to evaluate the importance of second opinion assessment for diagnostic mammography and sonography in a breast cancer centre. Material and Method: We analysed a total of 374 diagnostic mammographies and sonographies. All patients had previously undergone mammography and sonography examination in different external clinics, and the findings had been classified according to the BI-RADS system. All patients underwent additional sonography investigation in the outpatient department of our university clinic with additional mammography where necessary. The final diagnosis (histological clarification in 316 cases, follow-up in 58 cases) was compared with the BI-RADS classification made by the external clinics and by the university clinic, and the correlation between their findings and the final diagnosis was analysed. Results: The final diagnosis yielded 146 benign lesions and 228 cancers. In 74 % of cases (277/374), the BI-RADS classification of the first assessment corresponded to that of the second assessment. 26/55 lesions (47 %) were upgraded at the second assessment from BI-RADS 3 to BI-RADS 4, and 71/186 findings (38 %) were downgraded at the second assessment from BI-RADS 4 to BI-RADS 3. The correlation between the initial diagnosis made in the external facilities and the final diagnosis was low (kappa: 0.263), but the correlation between the second opinion assessment and the final diagnosis was significantly (p < 0.001) higher (kappa: 0.765). The second assessment increased the sensitivity from 91 % (208/228) to 99 % (225/228) and the specificity from 32 % (46/146) to 74 % (108/146). 20 additional malignant lesions were only detected at the second assessment; however the second assessment also resulted in 3 additional false-negative findings. Surgical biopsy was prevented in 49 women after the second assessment. Conclusion: An independent second diagnostic evaluation can significantly improve the correlation between BI-RADS classification and the final diagnosis, resulting in a benefit for the patient.
Keywords: breast neoplasm; quality assurance; second opinion; BI-RADS